Social Policy of Science Viewed from the Aspect of Sociology - Research and some Discussions - Tran, Van Huan (H. : ĐHQGHN, 2020)
Sociology and social policy of science are one of the new sciences but full of potiential for development in Vietnam. This paper combines more methodologies to analyze the basic relationships of them by some aspects in practise. The consequences bring more new think, to be looked down on or even denied about relating between two these sciences.